Realistic Calculations for Cold Dark Matter Detection Rates - Kosmas, T. S.; Kortelainen, M.; Suhonen, J.; Toivanen, J. (HNPS Advances in Nuclear Physics, 2020)
The scattering of the cold dark matter (CDM) candidate LSP (Lightest Supersymmetric Particle) off nuclei is investigated. We focus on the nuclear-structure aspects of the LSP-nucleus scattering problem and computed the associated event rates as well as the annual modulation signals for the 23Na, 71Ga, 73Ge and 127I CDM detectors by using the nuclear shell model in realistic model spaces and exploiting microscopic effective two-body interactions. Large-scale computations had to be performed in order to achieve convergence of the results. The relevance of the spin-dependent and coherent channels for the event rates is discussed, from both the nuclear structure and the SUSY-model viewpoints.